Not as Bad as I Thought: Consumers' Positive Attitudes Toward Innovative Insect-Based Foods - Junges, Juliana Rotunno; do Canto, Natália Rohenkohl; de Barcellos, Marcia Dutra (Frontiers in Nutrition, 2021)
Considering that the demand for food will increase by 70% by 2050, the consumption of insect-based foods appears as an alternative to traditional proteins due to its nutritional quality and low environmental impact. However, there is a need to investigate the acceptance of these innovative foods, especially in traditional meat-eating markets, such as the one in Southern Brazil (land of the Gauchos). The purpose of this manuscript is to analyze consumers’ attitudes towards innovative insect-based foods. The methodological procedures were divided into two stages. In the qualitative stage, 14 interviews were conducted regarding meat consumption habits. In the quantitative stage, a survey was carried out with 433 consumers. A factor and cluster analysis were performed, and two different groups of consumers were found. The results clearly show a segment with positive attitudes towards insect-based foods. This group had a low degree of neophobia. The products were perceived as not tasty and disgusting, but they were considered modern, with high nutritional value, positive, safe, and beneficial to the environment. Appearance, price, and packaging, combined with flavor, proved to be the attributes considered by consumers as the most important for their acceptance.